Estudo do gene Nramp1 canino em macrófagos infectados com Leishmania (Leishmania) Chagasi. - Regina Bueno (2006)
Controlling canine visceral leishmaniasis (CVL) is a public health challenge and the development of new tools for controlling the disease is very important. The Nramp1 (natural resistance associated macrophage protein 1) gene is expressed by macrophages and it is associated with natural resistance to intracellular pathogens. The goal was to study the role of Nramp1 in resistance against CVL by looking for genepolymorphisms that could be employed for the development of a test to detect natural resistance. Peripheral blood was collected from 29 dogs for isolation of mononuclear cells and their differentiation on macrophages in culture, which were inoculated with L. chagasi promastigotes, after ten days in culture, when 75% of the cells had phagocytic activity and 84% were positive for CD14 onocyte/macrophage marker as assessed by flow cytometry. The two most phenotypically resistant dogs, which were the ones with lower levels of Leishmania survival intracellularly in macrophages, after 24 and 72 hour of infection, and the two most susceptible dogs, were selected for cloning of thefull length Nramp1 cDNA. The consensus sequence from the resistant and susceptible dogs were aligned, resulting in a 2022bp sequence (GenBank access number DQ784645) that was identical for the four studied dogs. Therefore no polymorphisms of the canine Nramp1 associated with resistance against leishmaniasis were identified inthis study.